PERANCANGAN SISTEM PENETAPAN TINGKAT KEPADATAN MULTI RUANG MENGGUNAKAN ESP32: PERANCANGAN SISTEM PENETAPAN TINGKAT KEPADATAN MULTI RUANG MENGGUNAKAN ESP32 - okta lestari, okta lestari; Asniar Aliyu, Asniar Aliyu; Arif Basuki, Arif Basuki (ReTII, 2022)
During the COVID-19 pandemic, all activities that involve large numbers of people are reduced to reduce the potential spread of the COVID-19 virus. So the number of people in a room is important in the current pandemic era. To assist in determining the capacity of the number of people in a room, a system can be created to count the number of people in the room so that the room is always in accordance with the predetermined capacity. Therefore, this study aims to create a system for counting the number of people in an IoT-based room using ESP32 as a control center, proximity sensor E18-D80NK to detect the presence of objects, 4x4 matrix keypad to enter the specified number of data, DC-DC buck converter step down as a voltage reducer so that the ESP32 and selonoid doorlock can function, LCD I2C and by using Blynk.